The risk premium factor a new model for understanding the volatile forces that drive stock prices - Hassett, Stephen D., 1961- (Wiley finance series ;, 2011)
"A radical, definitive explanation of the link between loss aversion theory, the equity risk premium and stock price, and how to profit from itThe Risk Premium Factor presents and proves a radical new theory that explains the stock market, offering a quantitative explanation for all the booms, busts, bubbles, and multiple expansions and contractions of the market we have experienced over the past half-century.Written by Stephen D. Hassett, President of Hassett Advisors, a specialist in value management, new venture strategy, development, and execution for high technology, web, and mobile businesses, the book convincingly demonstrates that the equity risk premium is proportional to long-term Treasury yields, establishing a connection to loss aversion theory. Explains stock prices from 1960 through the present including the 2008/09 "market meltdown" Shows how the S&P 500 has consistently reverted to values predicted by the model Solves the equity premium puzzle by showing that it is consistent with findings on loss aversion Demonstrates that three factors drive valuation and stock price: earnings, long term growth, and interest rates Understanding the stock market is simple. By grasping the simplicity, business leaders, corporate decision makers, private equity, venture capital, professional, and individual investors will fully understand the system under which they operate, and find themselves empowered to make better decisions managing their businesses and investment portfolios"--